Interpreting Engineering Drawings (sach photo) - Jensen Cecil H. (Thomson Delmar Learning, 2006)
Comprehensive, state-of-the-art training is the cornerstone of this popular guide that shows users how to create professional-quality engineering drawings that can be interpreted with precision in today?s technology-based industries. Clearly the most flexible, user-friendly book of its kind on the market, the seventh edition offers unsurpassed coverage of the theory and practical applications individuals need to communicate technical concepts in an international marketplace. All material is developed around the latest ASME drawing standards, helping readers keep pace with the dynamic changes in the field of engineering graphics.